Investigations into reliability, maintainability and availability of tunnel boring machine operating in mixed ground condition using Markov chains. (November 2019) - Agrawal, Anil Kumar; Murthy, V.M.S.R.; Chattopadhyaya, Somnath
Abstract: Drilling and blasting have been the important methods of making underground tunnels for irrigation, subways, metro-lines, drainage and defense. Of late TBM (tunnel boring machine) is considered as the best positive alternative, in view of several advantages offered such as smooth profile, automated faster tunneling rates, easy to implement controls, safe and economic tunneling under favorable conditions. It is a gigantic high performing machine, with minimum hassles of operation if selected and operated judiciously. Thus, this equipment is the best possible choice to obtain a high penetration rate at minimum cost. TBM performs various operations such as rock cutting, discharge of muck, ring building and shifting of rail track (TBM movement). These operations are connected serially having a provision to function in parallel. Considering the high initial cost and import dependence, development of methodologies to establish the reliability of the system is mandatory. The reliability analysis using markov modelling was carried out for an EPBTBM (earth pressure balance tunnel boring machine), being used in an irrigation tunnel, considering its suitability to analyze a continuous production system. Accordingly, the failure and repair rates of the different subsystems were critically analyzed and variability was fixed. Maximum availability can be obtained by increasing reliability and maintainability of the equipment. This paper reports the study on the reliability, maintainability and availability of an EPBTBM deployed for excavating an irrigation tunnel located in Central India and the impacts of these parameters on the progress of tunnel. Availability of EPBTBM was found to be 61% which increased to 70% by proper maintenance and proper planning. Highlights: EPBTBM performance depends on its reliability, maintainability and availability. Markov analysis concludes 40% decrease in reliability in 1.5 h of operation. Maintainability, M(t) increases with time from Ms (1) = 0.09 to Ms (20) = 0.99. Availability of EPBTBM is under study around 61%. Preventive maintenance increases availability of the EPBTBM from 0.61 to 0.70.